PARylation-mediated post-transcriptional modifications in cancer immunity and immunotherapy - Matsumoto, Kazuya; Matsumoto, Yoshinori; Wada, Jun (Frontiers in Immunology, 2025)
Poly-ADP-ribosylation (PARylation) is a post-translational modification in which ADP-ribose is added to substrate proteins. PARylation is mediated by a superfamily of ADP-ribosyl transferases known as PARPs and influences a wide range of cellular functions, including genome integrity maintenance, and the regulation of proliferation and differentiation. We and others have recently reported that PARylation of SH3 domain-binding protein 2 (3BP2) plays a role in bone metabolism, immune system regulation, and cytokine production. Additionally, PARylation has recently gained attention as a target for cancer treatment. In this review, we provide an overview of PARylation, its involvement in several signaling pathways related to cancer immunity, and the potential of combination therapies with PARP inhibitors and immune checkpoint inhibitors.